2015
DOI: 10.1016/j.neuropsychologia.2015.01.040
|View full text |Cite
|
Sign up to set email alerts
|

Bilingualism provides a neural reserve for aging populations

Abstract: It has been postulated that bilingualism may act as a cognitive reserve and recent behavioral evidence shows that bilinguals are diagnosed with dementia about 4-5 years later compared to monolinguals. In the present study, we investigated the neural basis of these putative protective effects in a group of aging bilinguals as compared a matched monolingual control group. For this purpose, participants completed the Erikson Flanker task and their performance was correlated to grey matter (GM) volume in order to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
165
5
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 203 publications
(195 citation statements)
references
References 68 publications
10
165
5
4
Order By: Relevance
“…And this was also the case when the potential effect of laboratory was eliminated. This is consistent with earlier findings that the bilingualism effect emerges partially in the tail of response distributions (Abutalebi et al, 2015;Calabria et al, 2011;Tse & Altarriba, 2012). It appears that, when these prolonged responses were trimmed or not recorded, group differences might have also been eliminated.…”
Section: Discussionsupporting
confidence: 93%
“…And this was also the case when the potential effect of laboratory was eliminated. This is consistent with earlier findings that the bilingualism effect emerges partially in the tail of response distributions (Abutalebi et al, 2015;Calabria et al, 2011;Tse & Altarriba, 2012). It appears that, when these prolonged responses were trimmed or not recorded, group differences might have also been eliminated.…”
Section: Discussionsupporting
confidence: 93%
“…Three of them were cross-sectional studies that reported no significant brain differences (Gold et al, 2013;Grogan et al, 2012;Ressel et al, 2012). In contrast, three other studies using different techniques/measures and (Mechelli et al, 2004), cerebellum (Pliatsikas et al, 2014), left aITG (Abutalebi et al, 2014) and ACC (Abutalebi, Guidi et al, 2015). Each of the studies used different methods for the preprocessing and analysis of the data (see table 1).…”
Section: Discussionmentioning
confidence: 99%
“…This is the case for the IPL, which was initially demonstrated by Mechelli et al (2004) and then replicated by Grogan et al (2012) and but using a different methodology (namely, ROI-based rather than a whole-brain approach). And also for the ACC (Abutalebi, Guidi et al, 2015) but replication to support this finding is lacking.…”
Section: Assessing These Findings In the Light Of Abutalebi And Greenmentioning
confidence: 95%
See 2 more Smart Citations